Analisis Komunikasi dalam Dakwah Husain Basyaiban - Muh. Rezki Prasetyo; Sitti Hajar; Yuni Asriani; Kurniati Abidin (SABER : Jurnal Teknik Informatika, Sains dan Ilmu Komunikasi, 2025)
This study aims to analyze the communication strategies in Islamic preaching (dawah) employed by Husain Basyaiban, particularly through the digital platform TikTok. The research utilizes a quantitative approach to obtain in-depth and measurable data. Data was collected through interviews with Basyaiban’s followers and content analysis of his preaching materials on TikTok. The results indicate that Basyaiban’s relaxed, dialogic, and audience-adaptive communication style effectively enhances the delivery of Islamic messages. Furthermore, the use of digital media such as TikTok has proven capable of reaching a wider audience and facilitating more dynamic interactions between the preacher (dai) and the congregation (mad’u). These findings highlight the importance of adapting preaching methods to technological advancements and audience characteristics in the digital era.